The complete iOS 11 and Swift developer course : build 20 apps - Walter, Nick (Packt Publishing, 2019)
"Use XCode 9 & Swift 4 to make real iOS 11 apps like Uber and Instagram, with CoreML & ARKit. Includes AWS Credit & more!"--Resource description page